Implementation of Learning Activities Using Recycled Materials in Kindergarten - Apriliana, Nur Indah; Nofiandri Eko Sucipto Dwijo, Al-Qudus; Mukhoyaroh, Mukhoyaroh; Abdelkhalek, Shafa (Indonesian Journal of Early Childhood Educational Research (IJECER), 2024)
Learning based on used materials for early childhood in an innovative approach that integrates environmental sustainability values with the development of creativity and fine motor skills. This study aims to describe the implementation of learning methods based on used materials in TK Muslimat NU Bunga Harapan, focusing on the benefits, challenges, and indicators of success. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the use of used materials, such as plastic, and kitchen waste, can support children's holistic development, skills, and recycling creativity. The obstacles faced include the limitations of certain used materials and children's negative perceptions of used materials as "trash". Indicators of success include children's enthusiasm in activities, work results, and active involvement in the process. This study concludes that the learning approach based on used materials is not only effective in supporting the development of early childhood, but also has the potential to be a relevant educational strategy in building environmental awareness from an early age.